Analisis Komposisi Fasa dan Parameter Unit Sel Kristal Hasil Kalsinasi Suhu Tinggi Abu Cangkang (Paguroidea) dengan Metode Rietveld - Mukminin, Amirul (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2019)
Quantitative analysis by data refinement of the Rietveld method for calcium-based catalyst samples from hermit crabs (Paguroidea) ash has been successfully carried out. The results of the improvement showed that the samples of hermit crab shell calcined at 900 ° C gave different phase compositions and unit cell parameters due to the influence of calcination times 2, 3 and 4 hours. 2 hours is a single phase CaCO3 calcite, 3 hours are multiphase CaCO3 calcite and CaO, while a 4 hour sample is a single phase CaO . The reliability value (R) of the improvement results, RP, Rwp, Rexp and GoF = χ2 gives good and acceptable results